MASS INDEX WITH QUALITY OF LIFE AMONG ADULTS AND ELDERS ASTHMA PATIENTS - Loriza Sativa Yan (Jurnal Vokasi Kesehatan, 2019)
Asthma ranked at first category of prevalence of chronic infectious diseases, in Indonesia asthma have been the highest cause of death and morbidity. Asthma called as a mild to severe chronic airway disease, which affected to quality of life. This study aimed to identify relationships between body mass index with the quality of life among adult asthma and elder’s people with asthma in Jambi City. Data collection techniques were carried out by total sampling method with a total sample of 69 respondents. The research instrument used Asthma Quality of Life Questionnaires (AQLQ). Data analyzed by Spearman test. The results showed that the majority of respondents were women with normally category in body mass index, and respondents who had a good quality of life. There was a significantly relationship between body mass index with quality of life among asthmatics patients. It is expected that health workers will be provide good counseling about nursing protection management to maintain an ideal body mass index and to improve quality of life for adult asthma patients